The impact of Schistosoma haematobium hybridization on molecular diagnosis of schistosomiasis: A review with emphasis on female genital schistosomiasis. - Ombeni Ally; Bernard N Kanoi; Gideon S Mmbando; Steven Ger Nyanjom; Ladslaus L Mnyone; Jesse Gitaka; Gerald Misinzo; Lucy Ochola (PLoS Neglected Tropical Diseases)
Female genital schistosomiasis (FGS) is a gynecological manifestation of urinary schistosomiasis in female genitals. FGS is a neglected tropical disease; not only are most patients unaware of the condition, but healthcare workers and policymakers have inadequate knowledge about it. The treatment and control of FGS relies on current guidelines for controlling and eliminating schistosomiasis without rigorous focus on clinical evidence of the presence of FGS. Neglect of FGS has led to the misconception that the disease is sexually transmitted. Diagnosing FGS remains challenging as there is no widely accepted reference assay. Urine examination, which is the gold standard in urogenital schistosomiasis has some limitations in diagnosing FGS as the demonstration of Schistosoma haematobium and/or eggs alone does not necessarily indicate FGS. In order to overcome challenges with the biopsy and colposcopy approach, some studies have evaluated the potential of PCR-based assays and isothermal amplification of Schistosoma DNA. Recent studies have reported hybridization between S. haematobium and other livestock schistosomes, but little is known about the impact of hybridization on schistosomiasis diagnosis. These hybrids not only affect livestock and humans but also have their genomes modified, and in some cases, abnormal egg morphology due to Schistosoma hybridization might affect the actual prevalence estimation. Herein, we highlight the potential impacts of S. haematobium hybridization on molecular diagnosis of schistosomiasis, with an emphasis on FGS.